(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
In a diverse and fractured post-colonial society, schools need to take cognizance of the multi-faceted perspectives of heritage represented within the school community. A healthy debate between the various segments of the society of which a school is but a microcosm, needs to be facilitated and consensus reached on the recognition of a common humanity and the rights of citizens in a complex and vibrant nation. It is in the minutiae of that which is to be found in local history, and the pride that the preservation thereof instils in communities regarding their heritages and their place in the world, that a sense of belonging and, ultimately, good citizenship is fostered. Embracing previously ignored heritage does not necessitate “wiping the slate clean”. The citizenry will be left poorer in the intellectual and historical debate if the net is not cast wide enough and the emphasis falls upon exclusion and segmentation rather than the need to embrace.